Services Policy Review: Paraguay (II) - United Nations Conference on Trade; Development (United Nations, 2021)
Undertaken by UNCTAD at the request of the Ministry of Industry and Trade (MIC) of Paraguay, this review supports the role of services in diversifying and improving economy and trade in the country. It evaluates bottlenecks and opportunities to pursue development gains from services, first presenting a related economic and trade assessment. It subsequently analyses Paraguay’s development strategies, trade negotiations and other initiatives in services, before offering detailed assessments on fluvial transport services and professional services associated with the construction sector. Finally, it concludes with an analysis of cross-cutting and makes sectoral-specific policy recommendations.